Correlation between Science and Education Lecturers’ Perceived Use of Google Classroom for Instruction - Akpeji, Peace; Obielodan, Omotayo Olabo; Onojah, Amos Ochayi; Onojah, Adenike Aderogba; Abdulrahman, Mohammed Rabiu (Universitas Pendidikan Indonesia, 2022)
Technology has gained importance in all stages of education, yet educators have been unable to figure out which of the many available technological tools best fit their classroom practices. Google Classroom is one such tool that is free of cost and has gained popularity quickly. This study investigates the perceived use of google classroom among science and education lecturers and their relationship. This study, which uses the questionnaire method, consists of 150 lecturers who have implemented Google Classroom for at least one semester in their classroom. Findings revealed that lecturers positively perceive Google Classroom if all the necessary resources and environments are implemented. It has a user-friendly interface, and it saves time tremendously. It concludes that google classroom has a long-term future in instruction at the university of Ilorin provided the application keeps upgrading to meet user needs. This implies that adequate access to the internet and intelligent digital tools are the major drawbacks to the use of google classroom. It was, however, recommended that if deliberate efforts are channeled towards internet connectivity and availability of useable computers, it would go a great length